2022
DOI: 10.1186/s13005-022-00332-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of bioceramic sealer iRoot SP extrusion in root canal treatment: a retrospective analysis

Abstract: Background During the obturation procedure, sealer extrusion occurs in some cases. iRoot SP is a kind of bioceramic sealer with superior physicochemical and biological properties. This article reports the outcome of iRoot SP extrusion in root canal treatment and the potential factors associated with the outcome. Methods Ninety-nine patients and one hundred and eighty-five teeth treated between 2014 and 2020 were included in this retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…According to a randomized clinical trial, iRoot SP resulted in a similar clinical performance and success rate to an epoxy resin‐based sealer at a 2‐year follow‐up when used with a warm vertical compaction technique 163 . One of the most commonly used root‐filling techniques with CSSs in clinical studies was the single cone technique 164–166 . According to a retrospective study using iRoot SP sealer with a single cone technique, the success rate was 96.8% and iRoot SP extrusion had no adverse effect on the treatment outcome 164 .…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…According to a randomized clinical trial, iRoot SP resulted in a similar clinical performance and success rate to an epoxy resin‐based sealer at a 2‐year follow‐up when used with a warm vertical compaction technique 163 . One of the most commonly used root‐filling techniques with CSSs in clinical studies was the single cone technique 164–166 . According to a retrospective study using iRoot SP sealer with a single cone technique, the success rate was 96.8% and iRoot SP extrusion had no adverse effect on the treatment outcome 164 .…”
Section: Introductionmentioning
confidence: 90%
“…163 One of the most commonly used rootfilling techniques with CSSs in clinical studies was the single cone technique. [164][165][166] According to a retrospective study using iRoot SP sealer with a single cone technique, the success rate was 96.8% and iRoot SP extrusion had no adverse effect on the treatment outcome. 164 In prospective studies, similar success rates were reported for the single cone technique using BioRoot RCS and warm vertical compaction technique using an epoxy resin-based sealer 165 or a zinc oxide-eugenol sealer.…”
Section: Root Canal Sealermentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, most root canal filling techniques are based on the use of a core material i.e., gutta-percha, and an endodontic sealer. Whether cold-based techniques i.e., lateral condensation or single-cone, or techniques involving heat i.e., warm vertical compaction or continuous wave, endodontic sealers may extrude to a variable extent from the apical foramen or accessory canals and into the periodontium [ 2 , 3 ]. Thus, they should at least exhibit an adequate cyto- and biocompatibility, meaning that when placed in contact with surrounding periodontal cells and tissues, respectively, no negative responses nor alterations in their physiological functioning should be expected [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first bioceramic or HCSB root canal sealer accompanied by the favorable properties of bioceramic cements was introduced in 2008, under the brand name ProRoot Endo Sealer (Dentsply Tulsa Dental Specialties, Charlotte, NC, USA) [ 9 ]. Since then, numerous HCSB sealers that exhibit advanced biological properties, such as biocompatibility and bioinductivity, have been launched commercially and used in clinical practice, including TotalFill BC Sealer (FKG, La Chaux de Fonds, Switzerland), Bio-C Sealer (Angelus, Londrína, PR, Brazil), EndoSequence Bioceramic Sealer (Brasseler USA, Savannah, GA, USA), and iRoot SP Sealer (Innovative BioCeramix Inc., Vancouver, BC, Canada) [ 10 11 12 ].…”
Section: Introductionmentioning
confidence: 99%